The productive logic of advertising in a short story by Primo Levi (Comunicação & Inovação, 2015)
The discourse of contemporary advertising increasingly disseminates itself in the means of mass communication and adapts itself to the new media platforms. Its production logic spreads itself throughout other types of textualities, which are propagated by the media and it consolidates itself as a form of publicisation of everyday life. As we did in some other studies, we will investigate aspects of consumption and of advertising rhetoric by means of a fictional text of world literature. This time we chose the short story "Written on the Forehead", by the Italian writer Primo Levi. We will mobilise concepts of French Discourse Analysis, of literary theory and of the language of advertising - which leads us to discuss the dissemination strategy of contemporary advertising by means of the fictional narrative in question.
Keywords: Consumption. Literature. Advertising.